Management of severe community-acquired pneumonia in Brazil - Rabello, Lígia (2019)
Objective: This study aimed to evaluate Brazilian physicians' perceptions regarding the diagnosis, severity assessment, treatment and risk stratification of severe community-acquired pneumonia patients and to compare those perceptions to current guidelines. Methods: We conducted a cross-sectional international anonymous survey among a convenience sample of critical care, pulmonary, emergency and internal medicine physicians from Brazil between October and December 2008. The electronic survey evaluated physicians' attitudes towards the diagnosis, risk assessment and therapeutic interventions for patients with severe community-acquired pneumonia. Results: A total of 253 physicians responded to the survey, with 66% from Southeast Brazil. The majority (60%) of the responding physicians had > 10 years of medical experience. The risk assessment of severe community-acquired pneumonia was very heterogeneous, with clinical evaluation as the most frequent approach. Although blood cultures were recognized as exhibiting a poor diagnostic performance, these cultures were performed by 75% of respondents. In contrast, the presence of urinary pneumococcal and Legionella antigens was evaluated by less than 1/3 of physicians. The vast majority of physicians (95%) prescribe antibiotics according to a guideline, with the combination of a 3rd /4th generation cephalosporin plus a macrolide as the most frequent choice. Conclusion: This Brazilian survey identified an important gap between guidelines and clinical practice and recommends the institution of educational programs that implement evidence-based strategies for the management of severe community-acquired pneumonia.